A Comparison of Coordination Variability of Lower Extremity Segments in Men with Genu Varum and Healthy Men during Treadmill Running at Different Speeds: A Cross-Sectional Study - Mehdi Arabkhazaeli; Ali Abbasi; Mehdi Khaleghi-Tazji; Amir Letafatkar (Vesnu Publications, 2020)
Introduction: The purpose of this research was to compare the coordination variability of lower extremity segments in men with genu varum and healthy men during treadmill running at different speeds.Materials and Methods: Among sports and physical education students, 15 healthy men and 15 men with genu varum voluntarily participated in this research. Each participant ran on treadmill for 60 seconds at preferred speed and 25% faster and 25% slower than preferred speed. The kinematics data of lower extremities were collected by MyoMotion motion analysis system at 200 Hz sampling frequency. Coordination calculations were done by continuous relative phase (CRP) method for three segments coupling and compared between two groups.Results: The results of repeated measures analysis of variance (ANOVA) between groups showed that coordination patterns of segments did not differ significantly between the groups during running at different speeds (P ˃ 0.05). However, the change in running speed caused significant differences in coordination and coordination variability of segments in some phases of running in two groups (P ≤ 0.05).Conclusion: Coordination pattern of segments during running seems the same between genu varum and healthy groups; however, significant differences in these patterns and different running speeds were evident in both groups. On the other hand, coordination variability of segments was not different between groups, but the increase in running speed reduced the coordination variability during early and late swing and mid-stance phase of running in both groups. This finding may imply higher risk of overuse injuries at these phases.